TINJAUAN YURIDIS PENYELESAIAN SENGKETA KEPAILITAN TERHADAP ADANYA KLAUSUL ARBITRASE - mahdi surya (MORALITY: Jurnal Ilmu Hukum, 2017)
Abstract : Research review of juridical dispute resolution bankruptcy against the existence of the arbitration clause, have the problem of how the basic dispute resolution Authority Bankruptcy and Insolvency with dispute resolution arbitration clause based on the principle of Pacta Sunt Servanda. This research uses the normative research methods to analyze legislation related to bankruptcy dispute resolution in Indonesia. From this research it can be noted that with the enactment of Act No. 37 of the year 2004, then bankruptcy dispute resolution authority is the authority of the courts of Commerce according to article 1 of law No. 37 number 7 Year 2004 where it determines that the article in question in court in Act No. 37 of the year 2004 is the Commerce Court. Furthermore, problems associated with the bankruptcy dispute resolution based on the existence of an agreement between the two sides in agreement that acknowledged the existence of the arbitration clause as an attempt of dispute resolution in accordance with the principle of pacta sunt servanda, then the issue of dispute settlement, bankruptcy court but no longer authorized commercial arbitration institutions is authorized. This is because as one form of high penjunjungan the legal principles of the agreement, namely the principle of pacta sunt servanda that diimpelementasikan in the provision of article article 3 Law Number 30 of 1999 on alternative dispute resolution and Arbitration, stating that the State Court is not uthorized to adjudicate disputes of parties who have been bound in the arbitration agreement. Keywords : bankruptcy, arbitration, the principle pacta sunt servanda